Pengaruh Free Cash Flow terhadap Kebijakan Hutang - Lulu Almarjan; Deni Muhammad Danial; Dicky Jhoansyah (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aims to determine how much influence the free cash flow on debt policy at PT Indofood Sukses Makmur Tbk. The method used in this research is descriptive and associative methods with quantitative approaches. The data used is PT Indofood's annual financial statement data for 8 years from 2011 to 2018. The statistical test used is calculation, analysis using simple linear regression including the coefficient of determination test. The results showed that the free cash flow variable gained a significance value of 0.008, which means that there was an influence of free cash flow on the corporate debt policy of PT Indofood Sukses Makmur Tbk. Conclusion, there is a significant influence and strong relationship with the positive direction of the variable free cash flow (free cash flow) on the debt policy at PT Indofood Sukses Makmur Tbk. Keywords: Free Cash Flow, Debt Policy